PENERAPAN AKAD MUSAQAH TERHADAP BAGI HASIL KEBUN KARET DI DESA PASAK KECAMATAN SUNGAI AMBAWANG - Nofal; Hasan, Muhammad; Qomaruzzaman, Qomaruzzaman (Al-Aqad, 2025)
This study aims to examine the characteristics and qualifications of the parties involved in the musaqah contract within the practice of profit-sharing arrangements in rubber plantations in Pasak Village, as well as the content of the musaqah contract and the sighat (contractual declaration) used in this practice in Pasak Village, Sungai Ambawang Subdistrict. The research employs a qualitative method with a normative-empirical legal research approach. Data sources include primary data and secondary data such as books, journals, theses, and articles. Data collection techniques involve interviews and documentation. The data analysis technique used by the researcher consists of data collection, data reduction, data presentation, and drawing conclusions. The findings indicate that: 1) The characteristics of the musaqah contracting parties are primarily driven by economic and social motivations, such as limited capital, aspirations for fairness, and the need to fulfill family necessities. Technical competence and practical experience are considered more important than formal educational background, with cooperative relationships typically lasting between seven to ten years; 2) The content of the musaqah contract includes the division of responsibilities, profit-sharing ratios (60% to the cultivator and 40% to the landowner), and marketing mechanisms. Participatory negotiation processes and periodic evaluations help maintain the relevance and fairness of the agreement; 3) The sighat is performed informally through oral declarations, handshakes, and recitation of "bismillah" (in the name of God) in the presence of witnesses. Although not documented in writing, this form of sighat is regarded as valid and morally and spiritually binding, reflecting an adaptation of Sharia principles to local customary norms.